Semiotics Analysis of Dynamics LPM Magazine Cover “Uber-Uber Manusia Silver” November 2020 Edition - Putri Ayu Dahniar Harahap; Muhammad Alfikri (PT Mattawang Mediatama Solution, 2022)
The cover of the LPM Dinamika magazine discusses the silver man phenomenon that occurs in Indonesia, the lack of a solution from the government that causes them to take to the streets, and the higher income required to become a silver man. The goal of this study was to figure out what the representamen, objects, and interpretants on the magazine cover meant. This study employs a descriptive qualitative method, with the cover of this magazine serving as the material for analyzing Charles Sanders Pierce's semiotics. The researchers chose the cover of the Silver Man magazine as material that is considered quite interesting and needs to be studied out of the many magazine covers studied. The two elements contained on the cover, namely visual elements in the form of images and text elements in the form of typography, show the results of this study, users of the sign on the cover of Uber-Uber Human Silver dynamics. Seven marks were discovered on the cover as a result of these two elements.